A new species of Paratus Simon, 1898 (Araneae: Liocranidae, Paratinae) from India - Sankaran, Pradeep M.; Malamel, Jobi J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2017)
Paratus Simon, 1898 is a small and ill-defined liocranid genus distributed in the Oriental region (World Spider Catalog 2017) at altitudes of 27 (present data) to 2020 metres (Guchengshan [Zhao & Peng 2013]). Simon (1898) proposed this genus for a single female from Sri Lanka (Kandy) described as Paratus reticulatus Simon, 1898. Since the original description of the genus (Simon 1898) failed to provide diagnostic illustrations, the genus, after its erection, received no significant taxonomic treatment and remained dormant for a period of 103 years, until Deeleman-Reinhold (2001) re-examined and provided a detailed, illustrated redescription of the type of P. reticulatus, placing Paratus among ‘Liocraninae s.l. incertae sedis’. Marusik et al. (2008) revised, rediagnosed the genus, and assigned it into a newly proposed subfamily, Paratinae Marusik, Zheng & Li, 2008. The genus currently comprises five nominal species, two of which are known from both sexes, two only from males, and one only from the female (World Spider Catalog 2017). In this paper we describe a new species of Paratus from southern India, known from both sexes. Additionally the distribution of all known Paratus spp. is mapped.